Assessment of Shoreline Changes along Batu Pahat Coastline Using Digital Shoreline Analysis System - Hayazi, Fitrah; Mokhtar, Mardiha; Effendi Daud; Nor Baizura Hamid; Mohammad Ashraf Abd Rahman (Journal of Science and Technology, 2026)
Coastal areas particularly in Malaysia are among the most vulnerable regions that poses a significant risk to the local ecosystem and communities. This research aims to assess shoreline changes along Batu Pahat coastal area using the Digital Shoreline Analysis System (DSAS) over 10 years period which is from 2015 to 2024. Satellite imagery from Landsat 8 and Landsat 9 was utilized with DSAS to monitor the shoreline changes throughout the seven identified study areas along Batu Pahat coast. Three statistical indicators were selected to assess the shoreline changes which are the End Point Rate (EPR), Net Shoreline Movement (NSM) and Shoreline Change Envelope (SCE). The findings reveal that Batu Pahat coast was more exposed to erosion than accretion with the percentage of 50.62% and 49.38% respectively. Based on the End Point Rate (EPR) analysis, the maximum erosion rate recorded was -9.42 m/year whereas the maximum accretion rate reached 32.31 m/year, indicating significant spatial variability in shoreline changes. These findings provide valuable insight regarding the current condition of the coastal area thus appropriate mitigation can be implemented to protect the coastline.